A case of primary cardiac angiosarcoma with surgical resection and reconstruction. Issue 2 (February 2022) - Yada, Masashi; Tara, Yuichi; Sato, Shun; Sekine, Yuji; Nishina, Takeshi; Yamanaka, Kazuo; Ueda, Yuichi
Abstract: We report a 52-year-old man with primary cardiac angiosarcoma. He was referred to our hospital with a 3-month history of facial swelling and peripheral edema. Echocardiography and chest computed tomography revealed massive pericardial effusion and a right atrial tumor with a broad base at atrial septum which was extended into superior vena cava. We performed complete resection of the tumor and reconstruction of left atrium, atrial septum, right atrium, and superior vena cava with autologous pericardium and bovine pericardium. Histological examination exhibited angiosarcoma and a sign of radical excision. The patient, who made an uneventful recovery, was given postoperative radiotherapy and chemotherapy for liver metastasis 4 months postoperatively. The patient remains well without any signs of other metastasis for 2 years. We consider that an aggressive approach to resection with extensive reconstruction and multidisciplinary treatment can improve survival. Learning objective: Primary cardiac angiosarcoma is the most common primary malignant heart tumor with poor prognosis. We report a case of a 52-year-old man with primary cardiac angiosarcoma. We performed complete resection of the tumor and reconstruction of left atrium, atrial septum, right atrium, and superior vena cava with autologous pericardium and bovine pericardium. We think aggressive surgical resection with reconstruction is a feasible option.>